2022
DOI: 10.26559/mersinsbd.972603
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of nursing students on clinical practices

Abstract: Aim: The aim of this study was to determine the views of nursing students on clinical practices. Method: The population of the cross-sectional study consists of second, third and fourth year students (N=695) studying at a state university in the south of Turkey between 20 December 2019 and 15 January 2020, and the sample was consisted of 252 students. Data were collected by Personal Information Form and Nursing Students' Views of Clinical Practice Questionnaire. Analyzes were evaluated with percentage, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This recommendation applies to students in the immigrant health center and those in other clinical units. Previous studies found that students’ feedback encouraged teaching staff to spend more time in program centers (Altundal et al, 2022; Öner & Karabudak, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation applies to students in the immigrant health center and those in other clinical units. Previous studies found that students’ feedback encouraged teaching staff to spend more time in program centers (Altundal et al, 2022; Öner & Karabudak, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde; öğrencilerin, hastalara doğru sorular sormada güçlük yaşadıkları (13), hastadan, hasta yakınından ve sağlık personelinden olumsuz tepki almaktan çekindikleri için daha çok hasta dosyalarındaki verilere ulaşma eğiliminde oldukları, hasta/hasta yakını ve sağlık personeli ile iletişim kurmakta güçlük çektikleri, mahremiyetin sağlanamadığı kalabalık hasta odaları ve kliniğin gürültülü olması gibi faktörleri de engel olarak gördükleri vurgulanmaktadır. (14) Araştırmamızda öğrencilerin yarısına yakını kapsamlı veri toplama konusunda kendilerini "bazen" yeterli bulduklarını ve günlük yaşamlarında kişilerarası ilişkilerde ise "nadiren" zorluk yaşadıklarını belirtmiştir (Bkz. Tablo 5 Bireyden kapsamlı şekilde veri toplamak hayati önemi olan bir beceridir.…”
Section: Discussionunclassified
“…(4,5) Nitekim, hemşirelik öğrencilerinin veri toplamaya ilişkin bilgi düzeylerini ortaya koyan sınırlı sayıdaki çalışmada da hemşirelik öğrencilerinin veri toplama ile ilgili bilgilerinin yetersiz olduğu (6,7) ve veri toplama basamağının çeşitli aşamalarında güçlük yaşadıkları belirlenmiştir. (8)(9)(10)(11)(12)(13)(14)(15)(16) Yapılan bazı çalışmalarda da hemşirelik eğitim müfredatının veri toplamaya ilişkin öğrenme gereksinimlerini karşılamadığı, öğrencilerin klinik ortamda öykü alma konusunda sınırlı deneyime sahip oldukları (5) ve hastalara mahrem konulara ilişkin soru sormanın hemşirelik öğrencileri için bir stres kaynağı olduğu belirtilmektedir. (17,18) Bu sebeplerle, hemşirelik öğrencileri veri toplarken sıklıkla bireyin fiziksel yönüne odaklanmakta ve holistik bir hemşirelik planı hazırlama konusunda yetersiz kalmaktadır.…”
Section: Introductionunclassified
“…In particular, clinical practices enable students to gain competence in the use of values, attitudes, knowledge and skills related to the profession. Although touching the patient, understanding him/her, enabling him/heraltun to come from one stage to another stage, teaching nursing students roles and responsibilities and enabling them to gain professional competence (Çevirme and Kurt 2020;Altundal et al, 2022), clinical practice-based learning is among the situations that cause the most stress and anxiety in nursing students (Moridi et al, 2014). In the studies conducted, it has been stated that nursing students who will begin clinical practice for the first time experience stress due to reasons such as fear of making mistakes and harming the patient, anxiety…”
Section: Introductionmentioning
confidence: 99%